Previous antibiotic treatment as a risk factor for recurrent vulvovaginal candidiasis - Yang, Wen; Nie, You; Wang, Shujuan; Wang, Hongwei; Zhao, Enfeng; Dou, Na (Clinical Journal of Obstetrics and Gynecology, 2019)
The incidence of recurrent vulvovaginal candidiasis (RVVC) is extremely high. RVVC is likely to have a greater impact on patients. The aim of the study was to explore the risk factors of recurrent vulvovaginal candidiasis (RVVC) in the tropical coastal area. In this case-control study, a questionnaire survey was conducted in patients with VVC in the Sanya area from July 2014 to December 2016. The data included demographic characteristics, host factors, and behavioural characteristics. According to the maximum number of symptomatic episodes per year, the participants were classified into a non-recurrent VVC (NRVVC; < 4 episodes/year, including the current one) group or a RVVC group (≥ 4 episodes/year, including the current one). Crude odds ratios were calculated for potential risk factors and were adjusted using logistic regression. All vaginal secretions of patients with RVVC were cultured. Of the 728 cases of VVC, 69.0% (502/728) were NRVVC, and 31.0% (226/728) were RVVC. Previous antibiotic treatment (adjusted OR: 4.41, p < 0.01), repeat abortion (p < 0.05), and vaginal lavage (adjusted OR: 1.62, p < 0.05) were significantly associated with RVVC. A total of 230 yeasts isolates were obtained from 226 patients. C. albicans were the predominant Candida species (194 strains) in all patients of VVC. Our results demonstrate that in the tropical coastal area, a significant association was found between previous antibiotic treatment and incident RVVC. Host factors may be the most important factors in the occurrence of RVVC.